2011
DOI: 10.1007/s00198-011-1822-8
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of femoral neck areal bone mineral density to volumetric bone mineral density, bone size, and femoral strength in men and women

Abstract: Purpose aBMD by DXA is widely used to identify patients at risk for osteoporotic fractures. aBMD is influenced by bone size (i.e., matched for vBMD, larger bones have higher aBMD), and increasing evidence indicates that absolute aBMD predicts a similar risk of fracture in men and women. Thus, we sought to define the relationships between FN aBMD (assessed by DXA) and vBMD, bone size, and FE-derived femoral strength obtained from quantitative computed tomography scans in men versus women. Methods We studied m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…It was also shown that areal BMD (aBMD) as investigated by DXA is highly influenced by bone size. Thus, larger bones display higher aBMD values, although vBMD (volumetric BMD as obtained by CT scans) proves to be identical [17,27]. Using vBMD the confounding factor of the femoral head size could be reduced.…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that areal BMD (aBMD) as investigated by DXA is highly influenced by bone size. Thus, larger bones display higher aBMD values, although vBMD (volumetric BMD as obtained by CT scans) proves to be identical [17,27]. Using vBMD the confounding factor of the femoral head size could be reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, BMD values of the selected sites were reported for each study both pre and post WBV treatment, as mean and standard deviation (SD). BMD values were reported in g/cm 2 as quantified by dual energy X-ray absorptiometry [19]. …”
Section: Methodsmentioning
confidence: 99%
“…Therefore, they suggested that hip BMD is an excellent test for predicting fracture risk in men. It is also suggested by Keyak et al [49] that femoral strength, strongly correlated with hip BMD [49,78,79], is a more powerful discriminatory tool for assessing hip fracture risk in men than in women. The difference in the association between hip BMD and hip fracture risk in men and women may justify the suggestion of using a sex-specific T-score, rather than the female-normalized one, for assessing hip fracture risk [48,80].…”
Section: Associations Between Hip Fracture Risk and Body Parametersmentioning
confidence: 96%